Developing an Android-Based Application for Arabic Grammar Learning Aligned with the Common European Framework of Reference (CEFR) - Nurdianto, Talqis; Zainuddin, Ghazali; Huda, Nurul; Amrulloh, M. Afif (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2025)
This research aims to develop an Arabic educational app that complies with the Common European Framework of Reference for Languages (CEFR) and can be downloaded from the Playstore. In addition, the study seeks to evaluate the authenticity, practicality, and effectiveness of Arabic language learning resources on the Android platform in accordance with CEFR standards. The approach taken in this application adheres to the research and development strategy known as the ADDIE model, which consists of five phases: analysis, design, development, implementation, and evaluation. This technique is applied to improve language skills by encouraging users to deduce correct answers using images, vocabulary, phrases, dialogues, grammar lessons, practice activities, quizzes, and puzzles presented in Arabic. All entry-level Arabic learning materials will be gathered in an application named "Tashol" which can be easily accessed and downloaded via the Playstore on mobile devices. As a result, this research is designed to support not only those learning Arabic but also anyone interested in gaining proficiency in the Arabic language. By utilizing the educational resource Tashol, learners can expand their vocabulary, memorize useful phrases, and understand the fundamentals of Arabic grammar, mastering materials at the A1 level to swiftly enhance their Arabic language skills. The results of this research indicate that the Tashol Android application includes A1 level Arabic learning resources, covering grammatical details, vocabulary enhancement, and relevant expressions, positioning it as a highly versatile educational tool readily available on the Playstore.